2003
DOI: 10.1247/csf.28.23
|View full text |Cite
|
Sign up to set email alerts
|

Roles of MAPKKK ASK1 in Stress-Induced Cell Death.

Abstract: ABSTRACT. Apoptosis signal-regulating kinase 1 (ASK1) is a ubiquitously expressed mitogen-activated protein (MAP) kinase kinase kinase that activates the c-Jun N-terminal kinase (JNK) and p38 MAP kinase signaling cascades. Recent findings from analyses of ASK1-deficient mice have revealed that ASK1 is required for apoptosis induced by oxidative stress, TNF and endoplasmic reticulum (ER) stress. In addition, several lines of evidence have suggested that ASK1 has diverse functions in the decision of cell fate be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
171
1
2

Year Published

2004
2004
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(182 citation statements)
references
References 54 publications
8
171
1
2
Order By: Relevance
“…Park et al (55) have found that Hsp70 can inhibit JNK activation in cells exposed to UV irradiation and that this inhibitory function is linked to the Hsp70 ability to directly bind JNK and suppress its association with and phosphorylation by MKK4. The anti-apoptotic activity of Hsp70 is also reflected by its capacity to interact with apoptosis signal-regulating kinase 1, a mitogen-activated protein kinase kinase kinase of the JNK and p38 MAPK (mitogen-activated protein kinase) signaling pathways that is required for cytokine-and stress-induced apoptosis (56). In this case, Hsp70 binding prevents both oligomerization of apoptosis signal-regulating kinase 1 (ASK1), an event required for its activation, as well as ASK1-dependent apoptosis (57).…”
Section: Discussionmentioning
confidence: 99%
“…Park et al (55) have found that Hsp70 can inhibit JNK activation in cells exposed to UV irradiation and that this inhibitory function is linked to the Hsp70 ability to directly bind JNK and suppress its association with and phosphorylation by MKK4. The anti-apoptotic activity of Hsp70 is also reflected by its capacity to interact with apoptosis signal-regulating kinase 1, a mitogen-activated protein kinase kinase kinase of the JNK and p38 MAPK (mitogen-activated protein kinase) signaling pathways that is required for cytokine-and stress-induced apoptosis (56). In this case, Hsp70 binding prevents both oligomerization of apoptosis signal-regulating kinase 1 (ASK1), an event required for its activation, as well as ASK1-dependent apoptosis (57).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to those ligands, ''Stress'' is an input representing environmental stress factors such as UV light or reactive oxygen species (33,34), and there is a nonregulated calcium pump (external calcium pump). Calcium pumps are regulated mostly by calcium and hormonal factors that are not included in the current network (35).…”
Section: Methodsmentioning
confidence: 99%
“…These are (i) Akt, a major regulator of apoptotic systems (24), (ii) the mitogen-activated protein kinase (MAPK) Erk, a major regulator of cell division (34), and (iii) Rac and Cdc42, two important regulators of cytoskeletal systems (28). The MAPK's SAPK and p38 are also outputs of the network, but they respond to stress and TNF/IL-1 (33,34), as documented in SI Text. The experiments in the present work involve ''stress-limited'' inputs, meaning that stress and TNF/IL-1 are at low, background levels.…”
Section: Methodsmentioning
confidence: 99%
“…The JNK and p38 pathways are activated by corresponding upstream MAP2Ks, such as MKK4/7 and MKK3/6, respectively (6 -10). In contrast to the simple combinations of MAPKs and MAP2Ks, more than 10 MAP3Ks that control the JNK and p38 pathways have been identified to date, and it has not been clear which MAP3K contributes mainly to the stress-induced MAPKs pathway (11)(12)(13)(14). On the other hand, the transcriptional activity of NF-B is regulated by IB kinase (IKK)-mediated degradation of IBs and subsequent nuclear translocation of the NF-B complex (15).…”
mentioning
confidence: 99%